Influence of Different Copolymer Based Compatibilizers on Performance of Pristine and Recycled PP/PE blends - Rosales, Caren Soledad (2020)
One of the big engineering challenges in recycling thermoplastics is to manufacture competitive products in terms of mechanical properties such as toughness or strength. This process by which recycled waste is transformed into materials with improved performance, adding value and widening their application field, is known as upcycling. One of the strategies to improve PE/PP blends performance is to add a special compatibilizer, and this is the aim of the present work. To achieve this objective, four different commercial masterbatch compatibilizers based on copolymers were added to pristine blends. The compatibilizer that induced the best performance in virgin blends was selected to be applied in post-consumer recycled (PCR) blends, after minimizing its dosage to diminish costs. All blends were prepared simulating industrial processing conditions. Microstructure and morphology of blends were analyzed by DSC and SEM. Tensile and fracture studies were carried out at quasi-static loading conditions. Fracture surfaces were studied by SEM. It was observed that results found for pristine blends were consistent with those of recycled blends, and the addition of compatibilizing masterbatches improved the performance of both pristine and recycled PP/PE blends, in spite of the unpredictable composition and the presence of impurities of PCR blends.